Hybrid Hybrid Governance in Zakat Management: Integrating Pesantren Values and Transparency-Accountability Practices - Siti Nur ‘Afwiyyah; Joharul Fatoni (ICO EDUSHA, 2025)
This study aims to analyze the practices of transparency and accountability in zakat fund management at the Sharia Savings and Financing Unit (USPPS) of Darussalam Islamic Boarding School, Blokagung, Banyuwangi. Descriptive qualitative approach was employed, with data collected through interviews, observations, and document analysis. The results indicate that transparency practices remain informal and limited to internal announcements, lacking public reporting systems. Accountability relies on moral values and social trust but lacks systematic documentation and external audits.The primary constraints are limited human resources and digital infrastructure. The study concludes that governance strengthening through staff training, report digitalization, and stakeholder support is essential to develop a professional and accountable zakat information system based on good governance principles. Keywords: Transparency; Accountability; Zakat Management; Islamic Boarding School; Good Governance.